DIALOG DYDAKTYCZNY W UCZENIU SIĘ JĘZYKA OBCEGO - Karpińska-Szaj, Katarzyna; Sujecka-Zając, Jolanta (Neofilolog, 2019)
The article presents ‘didactic dialogue’ against the background of other interactive forms of remediation in foreign language learning. Drawing on the works of Antoine de La Garanderie, Reuven Feuierstein and Pierre Vermersch, three didactic approaches have been analyzed. Theoretical considerations have been illustrated with conclusions formulated on the basis of own studies on the use of dialogues in different educational contexts, which included: the diagnosis and remediation of language deficits of special educational needs students, remediation in the case of school failure in foreign language learning, and an interview after completing a task of retelling a story.